Cyber-noir: Cybersecurity and popular culture. Issue 1 (2nd January 2020) - Shires, James
ABSTRACT: Cybersecurity experts foster a perception of cybersecurity as a gloomy underworld in which the good guys must resort to unconventional tactics to keep at bay a motley group of threats to the digital safety of unsuspecting individuals, businesses, and governments. This article takes this framing seriously, drawing on film studies scholarship that identifies certain aesthetic themes as associated with moral ambiguity in noir films. This article introduces the term "cyber-noir" to describe the incorporation of noir elements in cybersecurity expert discourses. It argues that the concept of cyber-noir helps explain the persistence of practices that blur legal, moral, and professional lines between legitimate and malicious activity in cyberspace. Consequently, changing cybersecurity requires not only institutional and technological measures, but also a re-constitution of cybersecurity identities themselves.